Relación entre el clima institucional y desempeño docente en instituciones educativas de la Red N° 1 Pachacútec - Ventanilla - Pérez Huamán, Yolanda Maximiliana (2012)
The study aimed to establish the relationship between school climate and teacher performance in educational institutions of the network No. 1 Pachacutec Ventanilla. The sample was available, consisted of 100 teachers of educational institutions of the Network 1. The type of study was correlational and descriptive correlational design. We applied the institutional climate instrument developed by Martin (1999) and adapted by Perez (2010) for validation by experts, 0.98 and internal consistency reliability, Cronbach's alpha of 0.948. For teacher performance, we applied the test developed by Valdes (2004) and adapted by Salluca (2010), with validity and reliability of 0.98 0.915. Correlation was found between school climate and teacher performance, correlation also found in all dimensions of school climate with teacher performance. The study concludes that there is positive correlation between school climate and teacher performance in the educational institutions of the network 1 Ventanilla.